Decreased IGF-1 level is associated with restrained amino acid metabolism in NSCLC with diabetes mellitus - Lv, Hehe; Zhang, Fan; Liang, Can; Liu, Xuekui; Ma, Yamei; Li, Jiayi; Ye, Yan; Si, Shanwen; Liu, Yaran; Heng, Hao; Geng, Houfa (Frontiers in Endocrinology, 2022)
The discovery of a large number of small pulmonary nodules and early diagnosis of lung cancer in the diabetic patients prompt us to re-examine the relationship between diabetes and the occurrence and development of lung cancer. The aim of this study was to explore the underlying metabolites changes in diabetes with NSCLC or benign nodule patients, and further to investigate the association of serum IGF-1 level and differentially expressed metabolites (DEMs). An untargeted metabolomics method was used to detect the changes of metabolism in diabetic patients with NSCLC on the platform of HR-MS. Serum level of IGF-1 was measured by ELISA. The patients were divided to three groups, DM, DLB (nodule), and DLC (cancer). we have identified numerous DEMs, which include amino acid, choline, and fatty acid derivatives. Further analysis of the involved metabolic pathways suggested that linoleate metabolism, tryptophan metabolism, histidine metabolism, putative anti-Inflammatory metabolites formation from EPA, and arachidonic acid metabolism were considered to be the most significant metabolic pathways between groups. Networks analysis suggested that a series of metabolites were associated with serum IGF-1among the three groups, which can be divided into 6 categories. Nine metabolites have been identified as the main DEMs among the DLC, DLB, and DM groups. In conclusion, metabolomics is a powerful and promising tool for the cancer risk evaluation in diabetic patients. Our results suggest that decreased IGF-1 level is associated with restrained amino acid metabolism in NSCLC with diabetes mellitus.